THE ROLE OF INNOVATION IN CREATING DIFFERENCE THROUGH MARKETING STRATEGY - Mukhlisah; Nuraeni Kadir (Scientia Integritas Utama, 2023)
This study presents an overview of the role of innovation in creating differentiation through marketing strategies among food SMEs in Makassar City. This study was conducted with a qualitative and explorative approach. Informants in this study are MSME business actors. The sampling technique was carried out by snowball. Data was collected using in-depth interview techniques. Then the data were analyzed descriptively qualitatively with data reduction techniques, displaying data and drawing conclusions. The results of the study show that innovation and marketing are interrelated in supporting the sales of MSME products. Innovation is also a differentiator between one MSME and other MSMEs. Innovation can be done through a marketing strategy.